Abdul Fattah Abu Ghuddah’s Thoughts on Role Models in Islamic Education - Panggabean, Fajariah; Darlis, Ahmad (Academia Open, 2025)
Background: Role modeling (uswah hasanah) is a foundational element in Islamic education, rooted in the prophetic tradition. Specific Background: Abdul Fattah Abu Ghuddah, a prominent Islamic scholar, extensively emphasized the significance of role models in the tarbiyah process. Knowledge Gap: However, scholarly analysis of his contributions to the conceptual framework of role modeling in education remains limited. Aim: This study aims to examine Abu Ghuddah’s thoughts on role modeling and its relevance to contemporary Islamic educational practices. Results: Through qualitative library research and content analysis of his primary works, the study reveals that Abu Ghuddah viewed exemplary behavior not merely as a pedagogical method but as the essence of Islamic education, exemplified by the Prophet Muhammad. He proposed practical steps for integrating role models into education, such as adherence to Qur’anic and prophetic directives, alignment with sharia, and consistency between speech and action. Novelty: The study offers a structured interpretation of Abu Ghuddah’s model of role modeling, positioning it as a moral-epistemological foundation for modern Islamic pedagogy. Implications: These findings suggest the need for educational institutions to embed role model values into curricula and school culture to reinforce ethical and spiritual development alongside academic instruction. Highlights: Highlights role modeling as the core of Islamic educational practice. Emphasizes consistency between words and actions in educators. Proposes integrating prophetic values into school culture and curriculum. Keywords: Abdul Fattah Abu Ghuddah, Role Modeling, Islamic Education, Uswah Hasanah, Tarbiyah